(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The paper explicates in detail the interrelation between semiotics and stylistics in the context of affective discourse on social media, which is rapidly evolving in the online domain, where communication dynamics play a significant role in shaping public sentiment and interactions. While digital communications are growing, marked with varied forms of affect, the research regarding how semiotic and stylistic factors combine to constitute meaning and emotional resonance in such platforms remains incomplete. The main goals of the present research are to analyze semiotic resources employed in social media discourse and to investigate stylistic features that heighten affective involvement of users. Thus, a mixed-methods approach was adopted, where a qualitative and quantitative analysis was combined in order for the nature of affective discourses to be comprehensively covered. It includes all data on social media platforms such as Twitter, Instagram, and Facebook. The expressions of emotion, emojis, and language choices are further looked into. Preliminary results show that semiotic strategies-for instance, image, symbol, and certain linguistic features-play a vital role in driving users’ emotional responses and building community bonds. Moreover, stylistic devices such as tone, narrative structure, and even word choices go a long way in the expression and dissemination of an affective message. This again shows the complex interaction between language and emotion online. The findings herein presented not only provide an explanation of how affective communication works in digital environments but also contribute to more general discussions related to the impact of social media on expressions of emotions and on processes of identity formation.